(untitled) (Tribhuvan Journal, 2025)
This study aims to explore secondary school English teachers’ perceptions of CLIL. Narrative inquiry research design was used to collect data through in-depth interviews. Four teachers having a minimum of two years of teaching experience were selected purposively from four community schools located in Rupandehi, Nepal. Findings of this study reveal teachers’ positive perceptions of CLIL. Since CLIL integrates language and content learning, engaging teachers in an interactive and effective educational setting, it offers students opportunities to use language in meaningful contexts. The study promotes and increases student participation and their confidence in language learning. However, teachers lacked hands-on exposure to efficiently applying this approach in their real classrooms. The teachers face challenges due to inadequate teacher training, lack of resources and students’ poor English proficiency in implementing CLIL in ELT. The study can contribute to promote CLIL with teachers’ awareness and professional development.